Penggunaan Dimethyl Sulfoxide Sebagai Krioprotektan dalam Pembekuan Semen Ayam Kampung (THE USE OF DIMETHYL SULFOXIDE AS CRYOPROTECTIVE AGENT FOR NATIVE CHIKEN FROZEN SEMEN) - Junaedi, Junaedi; Arifiantini, Raden Iis; Sumantri, Cece; Gunawan, Asep (Jurnal Veteriner, 2016)
This study aim was to determine the best dimethyl sulfoxide (DMSO) concentration for native chicken’s(Gallus gallus domesticus) frozen semen. Semen was collected from three native chickens and then evaluatedmacroscopically and microscopically. Spermatozoa that used in this study had more than 75% spermmotility and more than 25 X 108 mL in sperm concentration. Semen was divided into three equal tubesand each of them diluted with Ringer lactate egg yolk (RLEY) extender consisted of 5, 7 and 9% of DMSO.Diluted semen was added into 0.25 mL of mini straw, then equilibrated at 5 °C for two hours. The semenwas then frozen placed in liquid nitrogen vapors for10 min. Finally, the semen was put into liquid nitrogenwith a temperature of – 196oC. Post thawing quality semen was assessed after 24 hours storage bythawing the straw in warm water (37 °C) for 30 seconds. Data were analyzed using one-way analysis ofvariance. The results demonstrated that the sperm motility and viability diluted with RLEY extenderwith 7% DMSO was better (p<0.05) than those in 5 or 9% DMSO. Semen quality decreased at every stepof freezing, especially between equilibration and thawing. Its concluded that 7% was the best DMSOconcentration for freezing of native chicken semen in Ringer lactate egg yolk extender compared to 5% and9%.
Keywords: frozen semen; native chicken; DMSO